건강정보이해능력과 개인의 특성이 스마트 헬스케어 이용 경험에 미치는 요인 분석 - 김가은(Ga Eun Kim); 박현준(Hyun Jun Park) (한국콘텐츠학회 논문지, 19(4), 2019)
As the paradigm of healthcare shifts from the center of treatment to the center of prevention, products and services related to disease prevention are emerging at domestic and abroad. The government considers the smart healthcare industry as a solution to healthcare problems such as an increase in the number of chronic illnesses and an increase in the burden of medical expenses. The purpose of this study is to explore the factors affecting the use of smart healthcare products and services focusing on Health Literacy and health related personal characteristics and to provide policy implications. The subjects of the questionnaire are 1,027 adults over 20 in the nation, and conducted an online survey. In addition, the factors were analyzed by decision tree method. As a result, most of the respondents(76.9%) did not have experience using Smart Healthcare products and services. However, in the Health Literacy question, there was a difference in use experience depending on the degree of difficulty in using the mass media information. Other factors were the degree of intention to use new technology, the understanding of counseling about family members and friends, and health checkups. In order to enable self-healthcare through smart healthcare products and services, the ability of consumers to explore and utilize health information from the mass media should be improved. In addition, government and enterprise efforts are needed to achieve this. 헬스케어의 패러다임이 치료 중심에서 예방 중심으로 변화함에 따라, 질병 예방과 관련된 제품 및 서비스가 국내외로 많이 등장하고 있다. 스마트 헬스케어는 만성질환자 수의 증가, 의료비 부담의 증가 등의 보건의료 문제점의 대안으로 언급되어 기업 및 정부는 산업 확산 움직임을 보여주고 있다. 기업은 웨어러블 기기, 앱 등의 형태로 제품 개발 및 출시를 하고 있고, 정부는 보건소를 중심으로 모바일 헬스케어 사업을 시행하고 있다. 본 연구는 소비자의 스마트 헬스케어 제품 및 서비스 이용에 미치는 요인을 건강정보이해능력(Health Literacy)와 건강관련 개인특성을 중심으로 탐색적 연구를 진행하고, 정책적 시사점을 제공하고자 한다. 전국의 20대 이상 소비자 1,027명을 대상으로 온라인 설문조사를 실시하고 의사결정나무 기법으로 요인을 분석하였다. 연구 결과, 응답자의 대부분(76.9%)은 사용 경험이 없는 것으로 나타났지만 건강정보이해능력 중 '대중매체 정보의 활용'의 어려움 정도에 따라 사용 경험에 차이를 보였다. 그 밖에는 신기술 활용 의향 정도, 주변인의 조언 이해, 건강검진 유무가 관련이 있는 것으로 분석되었다. 스마트 헬스케어를 통한 자가 건강관리가 가능하려면, 건강정보를 대중매체로부터 탐색하고 활용할 수 있는 소비자의 건강정보이해능력이 제고되어야하며 이를 위한 정부와 기업의 노력이 필요하다.